Right ventricular function and systolic pressure effect on survival of patients with tricuspid regurgitation. (25th November 2020) - Vaturi, O; Itelman, E; Kuperstein, R; Fefer, P; Barbash, I.M; Klempfner, R; Segev, A; Feinberg, M; Guetta, V; Maor, E
Abstract: : Severe tricuspid regurgitation (TR) is associated with poor outcome. The current analysis investigated the long term outcome of TR patients. Methods: Historical retrospective cohort of all cardiovascular patients evaluated at a tertiary heart center between 2007 and 2019. The current analysis included all patients who underwent echocardiographic evaluation. TR severity was extracted for all patients from the echocardiographic reports. Primary outcome was all cause mortality and was available for all patients from the national population register. Results: Final cohort included 97, 561 subjects, of whom 42, 187 (43%) were outpatients. Mean age was 66±17 and 55, 976 (57%) were men. Mild, moderate and severe TR was documented in 27, 389 (28%), 2, 871 (3%) and 1, 812 (2%) patients, respectively. During a median follow up of 50 months [IQR 22–83] 18, 476 (19%) patients died. Kaplan-Meier survival analysis demonstrated increased risk of death with increasing degree of TR (FIGURE; p Log rank <0.001). Multivariate cox regression with adjustment to age, gender, BMI and echocardiographic predictors of adverse outcome showed that compared with no or mild TR, patients with moderate or severe TR were 10% and 45% more likely to die (95% CI: 1.02–1.18, p=0.009 and 1.34–1.57 p<0.001 respectively). Interaction analysis with adjustment to known predictors of poor survival demonstrated that the association of severe TR with survival was dependent on right ventricle (RV) dysfunction and estimated RV systolic pressure (RVSP) with a more pronounced effect on patients with severe RV dysfunction (HR of 1.38 [1.07–1.80] vs. 1.09 [1.00–1.19], p for interaction = 0.01) and a more pronounced effect on patients with estimated RVSP <40 mmHg (HR of 1.60 [1.21–2.11] vs. 1.14 [1.03–1.25], p for interaction <0.001). Finally, a propensity score matching of patients with severe TR (N=1, 154) and matched controls with no or mild TR successfully demonstrated that patients with severe TR were 27% more likely to die during follow up (95% CI: 1.14–1.42, p<0.001). Conclusions: Severe TR is independently associated with poor survival. The association is modified by RV dysfunction and estimated RVSP. This report supports the need for studies to evaluate TR interventions on patients' clinical outcomes. Funding Acknowledgement: Type of funding source: None